Development of 3D multicellular liver organoids derived from human induced pluripotent stem cells to model antiretroviral therapy induced liver injury - Maepa, Setjie Welcome (Department of Integrative Biomedical Sciences (IBMS), 2025)
Introduction: The liver is an essential organ in the body responsible for the synthesis of serum proteins, biotransformation, and detoxification of xenobiotic drugs. Drug cytotoxicity studies have been conducted using cancer-derived cell lines which are inferior. In the present study, we developed and demonstrated the use of robust and tractable 3D multicellular human liver organoids (HLOs) to model drug induced liver injury (DILI) by exposing HLOs to Antiretroviral therapy drugs (ART), combination of ART and antituberculosis drugs (A+TB) and Schistosoma mansoni egg soluble antigen (SEA) or Troglitazone (TGZ). Methods: A quantitative reverse transcriptase-polymerase chain reaction (RT-qPCR) was adopted to confirm stage specific gene marker and we validated the presence of multiple cell lineages using flow cytometry. Enzyme-linked immunosorbent assay (ELISA) was employed to determine cytokine levels in ART/SEA/TGZ treated HLOs. A mass spectrometry-based proteomics approach was applied to decipher protein dynamics and molecular mechanisms of ART, A+TB and TGZ -induced liver injury in treated HLOs. Results: HLOs exhibited robust mature hepatic gene markers (CYP3A4, ATA1, ALB and HNF4-α), reduction in pluripotency (OCT-4, Nanog, and Sox2) and the definitive endoderm (SOX17 and GSC) markers. Flow cytometry using EpCAM, CD166 and CD68 antibodies indicated that HLOs comprise of 60,4% EpCAM+ cells, 11,2% EpCAM-/CD166+ cells and 5% EpCAM-/CD68+ cells, respectively. HLOs exhibited high CYP3A4 enzyme activity compared to HepaRG 3D model. Proinflammatory (IL-6, IL-1β and TNF-α) and anti-inflammatory (IL-4 and IL-10) cytokines were elevated in both models. IL-4 was more pronounced in SEA-treated HLOs only. Proteomic analysis successfully showed differentially expressed proteins (DEPs) in ART-HLOs, A+TB-HLOs (TGZ-HLOs compared controls. Functional enrichment of these DEPs in ART-HLO, A+TB-HLO and TGZ groups based on Gene ontology (GO), and KEGG pathway showed these proteins were associated with immunity and inflammation, oxidative stress, protein synthesis, neutrophil extracellular traps (NETs) formation, the ATP-dependent chromatin remodelling and necroptosis. Conclusion: We successfully generated multicellular 3D liver organoids consisting of hepatocytes, Kupffer cells and hepatic stellate cells. Proteomic data revealed that ART, A+TB and TGZ alters the expression of proteins mostly involved immunity and inflammation and mitochondrial functions, augmented oxidative stress, and necroptosis.